2014
DOI: 10.1021/es404512a
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Microbiological Characteristics during in Situ Chemical Oxidation and in Situ Bioremediation at a Diesel Contaminated Site

Abstract: While in situ chemical oxidation with persulfate has seen wide commercial application, investigations into the impacts on groundwater characteristics, microbial communities and soil structure are limited. To better understand the interactions of persulfate with the subsurface and to determine the compatibility with further bioremediation, a pilot scale treatment at a diesel-contaminated location was performed consisting of two persulfate injection events followed by a single nutrient amendment. Groundwater par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In addition, it has been reported that BOD 5 /COD ratios of crude petroleum were increased by the oxidation of Fenton's reaction, resulting in the enhancement of the biodegradability of petroleum compounds . Sutton et al also reported that concentrations of dissolved TPH and dissolved organic carbon (DOC) were increased after persulfate treatment at a diesel‐contaminated site. In addition, Sutton et al has demonstrated that DOC derived from diesel oxidation by Fenton's reagent was a preferential substrate for microorganisms.…”
Section: Resultsmentioning
confidence: 67%
“…In addition, it has been reported that BOD 5 /COD ratios of crude petroleum were increased by the oxidation of Fenton's reaction, resulting in the enhancement of the biodegradability of petroleum compounds . Sutton et al also reported that concentrations of dissolved TPH and dissolved organic carbon (DOC) were increased after persulfate treatment at a diesel‐contaminated site. In addition, Sutton et al has demonstrated that DOC derived from diesel oxidation by Fenton's reagent was a preferential substrate for microorganisms.…”
Section: Resultsmentioning
confidence: 67%
“…Whereas ISB has been successfully implemented following ISCO for the remediation of aliphatic and aromatic hydrocarbons [ 20 23 ], coupling chemical oxidation with an anaerobic bioremediation step for the treatment of chlorinated solvents is more challenging. In addition to the direct oxidative stress inflicted by the oxidant, increased oxidation-reduction potential associated with chemical oxidation may be detrimental to strictly anaerobic OHRB or other non-dechlorinating community members.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in pH is a disadvantage when using persulfate and is likely a primary reason for studies that noted detrimental effects in microbial density following persulfate oxidation [ 41 , 45 , 89 , 90 ]. In this study, pH was monitored and controlled to avoid microbial stress due to changing pH (data not shown).…”
Section: Resultsmentioning
confidence: 99%